2014
DOI: 10.5935/0101-2800.20140025
|View full text |Cite
|
Sign up to set email alerts
|

Depressed cardiac autonomic modulation in patients with chronic kidney disease

Abstract: CKD patients not yet on dialysis have reduced HRV, indicating cardiac autonomic dysfunction early in the course of CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Studies on arterial stiffness indices are in concordance to our results that PWV[ 18 19 20 21 22 23 ] in CKD Stage 4 and 5 predialytic patients is higher than controls while AI[ 23 ] is similar in predialytic patients and controls. On similar grounds, studies on predialytic CKD patients have found a reduction in HRV parameters[ 24 25 26 27 ] while there is paucity of studies in short-term (5 min) BPV. Recent literature has tried to decipher the mechanism responsible for reduced BRS in CKD patients by exploring the relationship between vascular (arterial stiffness) and neural (HRV) components[ 7 8 28 ] in renal transplant recipients and peritoneal dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on arterial stiffness indices are in concordance to our results that PWV[ 18 19 20 21 22 23 ] in CKD Stage 4 and 5 predialytic patients is higher than controls while AI[ 23 ] is similar in predialytic patients and controls. On similar grounds, studies on predialytic CKD patients have found a reduction in HRV parameters[ 24 25 26 27 ] while there is paucity of studies in short-term (5 min) BPV. Recent literature has tried to decipher the mechanism responsible for reduced BRS in CKD patients by exploring the relationship between vascular (arterial stiffness) and neural (HRV) components[ 7 8 28 ] in renal transplant recipients and peritoneal dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been supported that daily hemodialysis induced structural effects on the heart of uremic patients which was associated with alterations in HRV [97]. In particular, ANS dysfunction worsens as the disease progresses [98,99] and the duration of hemodialysis session increases [100] while age is an important player which contributes in the parasympathetic dysfunction often seen in CKD patients [101].…”
Section: Discussion-conclusionmentioning
confidence: 99%
“…Imbalances in autonomic control are increasingly being linked to chronic ECG abnormality in the literature ( Task Force of the European Society of Cardiology and the North American Society of Pacing and Electrophysiology, 1996 ; Sareban et al, 2020 ), especially in clinical populations (e.g., Smith, 1982 ; Binkley et al, 1991 ; Bigger et al, 1992 ; Algra et al, 1993 ; Kocovic et al, 1993 ; Hartikainen et al, 1996 ; de Oliveira et al, 2014 ). A relatively simple and non-invasive method that has shown promise for monitoring autonomic control is through heart rate variability (HRV) assessment, which is used to measure changes in intervals between successive heartbeats and is a non-invasive reflection of the health of the cardiac automatic nervous system (ANS) ( Rajendra Acharya et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%